A Polar Representation for Complex Interval Numbers - Lyra, Arão; Dória Neto, Adrião Duarte; Bedregal, Benjamın René Callejas; Trindade, Roque Mendes Prado (Revista de Ciência da Computação, 2019)
The present work defines the basic elements for the introduction to the Study of Complex variables under the mathematical interval context with the goal of using it as a foundation for the understanding of pure mathematical problems, associating the mathematical interval to support the results. The present article contributes to the complex interval theory taking into consideration Euler’s Identity and redefining the polar representation of interval complex numbers. In engineering, the present article could be used as a subsidy for many applications where complex variable theory is applicable and requires accurate results.